Acompañar abortos en Paraná. Reflexiones no metropolitanas sobre el activismo feminista en Argentina - Julia Burton (Mora, 2022)
This article analyses the feminist activism in Paraná from the study of Dora te Escucha –Dora Listens to you–, one of the fifty-four feminist collectives that are part of Socorristas en Red (feministas que abortamos) –Network of first responders (feminist who abort)–. In these pages the collective actions of this group are examined and some of the characteristics of the city of Paraná in relation to the activism for the legalization of abortion are analysed. This paper tries to constitute a contribution to the existing knowledge about feminism in Argentina from a situated and non-metropolitan perspective.